(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Transdermal patches of Papaverine Hydrochloride were prepared by the solvent casting method using ethyl cellulose, HPMC K15 and Sodium alginate using different ratios. The physicochemical parameters such as flexibility, thickness, smoothness, weight variation, moisture content, hardness and tensile strength were evaluated for the prepared patches. The formulation exhibited flexibility, uniform thickness and weight, smoothness, drug content, and moisture content. The in vitro diffusion studies were carried out using modified Franz diffusion cell using cellophane as the diffusion membrane and the formulation followed the Zero order diffusion and Higuchi’s diffusion kinetics. The stability studies indicated that all the patches maintained good physicochemical properties and drug content after storing the patches in different storage conditions. Compatibility studies indicated that there was no interaction between the drug and polymers. Hence, the aim of the present study was to prepare the sustained release formulation (Transdermal patches) of the drug using different blend of polymers. The formulated patches containing the hydroplilic polymers showed best release rate of drug.